Integrating Spiritual Values, Digital Transformation, and Legal Protection in Pesantren-Based Entrepreneurship: A TCCM-Based Systematic Review - Muhammad Anas; Umratul Khasanah; Nur Asnawi; Nuur Halimatus Sa’adiah Masrukhin (Department of Sharia Economics Faculty of Islamic Economics and Business, Islamic University of Syarifuddin Lumajang, 2026)
Non-Indexed Publication